Development of a Flipbook Learning Media for Macroscopic Fungi Identification in the Gumitir Pine Plantation - Wulandari, Dwi Intan; Maharani, Lila; Jayawardana, Hepta Bungsu Agung (Universitas Khairun, 2025)
This research aims to develop an innovative and effective flipbook learning medium based on the morphological identification of macroscopic fungi in the pine plantation area of Mount Gumitir. The background of this research is based on the lack of attractive and relevant teaching materials for tenth-grade students, especially in the material on biodiversity and the role of fungi in ecosystems. The research method used is the 4-D development model (Define, Design, Develop, Disseminate), which involves the stages of needs analysis, product design, development, and dissemination. Data collection was carried out in two stages: validation by experts (language, material, and media experts) and field trials on tenth-grade students at SMK Raudatul Ulum and SMK Bahrul Ulum. The instruments used included validation sheets for experts and student response questionnaires. The collected data were analyzed quantitatively and qualitatively to determine the feasibility and effectiveness of the flipbook as a learning medium. The results showed that the developed flipbook met the valid criteria from all experts, with an average score indicating a very good category after the revision process. Student responses also showed positive results, with most students stating that the flipbook was attractive and easy to understand, and helped them improve their understanding of macroscopic fungi. Thus, it can be concluded that this Mount Gumitir-based local potential flipbook has the potential to be an effective and innovative alternative learning medium to improve the quality of biology learning, especially fungi material